Educational Inclusion in High School: Analysis of Thirteen Investigations Published in Electronic Journals from 2012 to 2022: Inclusión educativa en bachillerato: análisis de trece investigaciones publicadas en revistas electrónicas de 2012 a 2022 (Papeles, 2023)
Introduction: The question that guides this work is what are the main categories that are identified in the articles published on educational inclusion in high school from 2012 to 2022 and what are the most outstanding characteristics of the research? For this reason, the objective of this work is to analyze the main categories and characteristics of research on educational inclusion at the high school level published in electronic journals from 2012 to 2022. Methodology: The research approach is qualitative, with a descriptive scope and documentary analysis. In the search engines, the words educational inclusion, high school and the name of two databases were placed: Redalyc and SciELO. Only investigations that included both aspects were chosen. Results and discussion: In total there are thirteen investigations that are analyzed. We proceeded to review each of the articles and to place the main data in a concentrate. Afterwards, the words that are related to educational inclusion were identified, among which the following stand out: democracy, decision-making, Special Educational Needs (SEN) from a broad vision; political, personal and educational barriers; learning barrier and people with disabilities. In addition, the categories related to options to enable educational inclusion are: programs, actions, technology and flexibility; educational practice and teacher training. Conclusions: It is concluded that although research on educational inclusion and high school is scarce; the one that exists provides elements to improve practices at that level and allow quality education for all. Although there are various barriers; there are also possibilities to innovate.
Keywords: Educational inclusion; High school; barriers to learning; tutorial; education technology